Synthesis of novel high primary hydroxyl functionality polyol from sunflower oil using thiol-yne reaction and their application in polyurethane coating. (September 2016) - Omrani, Ismail; Farhadian, Abdolreza; Babanejad, Niloofar; Shendi, Hasan Kashef; Ahmadi, Abbas; Nabid, Mohammad Reza
Graphical Abstract: Highlights: A novel biobased polyol was developed from sunflower oil. The polyol was synthesis in three facile steps. The polyol was used in polyurethane preparation. The prepared polyurethane shows unique properties. Abstract: In this study, novel bio-based polyurethanes that have characteristics of both thermosets and thermoplastics were prepared. The polyol functionalized by a high number of hydroxyl groups was synthesized and its application in polyurethanes, a well-known polymer in coating industry, was investigated. Sunflower oil was decorated for the first time with propargyl groups by ring-opening of epoxied groups using boron trifluoride diethyl etherate as catalyst. The polyol is obtained by photochemical thiol-yne coupling functionalization of propargylated oil in presence of mercaptoethanol in an economical, and environmental friendly procedure. The chemical structure of this sunflower based polyol and its intermediates were determined by 1 H NMR and FT-IR analysis. A series of polyurethanes containing various NCO/OH molar ratio were synthesized by a one-step procedure. The properties of the polyurethanes were studied by performing tensile testing, differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). A facile and green method for the synthesis of bio-based polyurethanes and their application as a transparent coating made them exponentially advantageous.